2020
DOI: 10.1055/s-0040-1719086
|View full text |Cite
|
Sign up to set email alerts
|

Lesão de Ombro após a Vacinação: Uma Revisão Sistemática

Abstract: ResumoAs reações adversas às injeções de vacina tendem a ser brandas e são incrivelmente raras. No entanto, vários casos de eventos em ombros, como bursite, dor generalizada ou diminuição da amplitude de movimento, foram relatados após vacinações de rotina. Esses eventos são conhecidos como lesões em ombro relacionadas à administração de vacina (SIRVA, do inglês shoulder injury related to vaccine administration).Uma revisão sistemática da literatura foi realizada para identificar todos os relatos publicados de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 41 publications
0
18
0
3
Order By: Relevance
“…The results of the study showed that only 12.3% of the participants had pain in their shoulder prior to the vaccine, while 69.1% had pain in their shoulder after the vaccine, indicating a significant increase in the number of participants with shoulder pain. Of those who reported pain after the vaccine, 50% rated their pain as average (4-6 on a scale of 1-10), 9% rated their pain as slight (1-3), and 41.1% rated their pain as severe (7)(8)(9)(10).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the study showed that only 12.3% of the participants had pain in their shoulder prior to the vaccine, while 69.1% had pain in their shoulder after the vaccine, indicating a significant increase in the number of participants with shoulder pain. Of those who reported pain after the vaccine, 50% rated their pain as average (4-6 on a scale of 1-10), 9% rated their pain as slight (1-3), and 41.1% rated their pain as severe (7)(8)(9)(10).…”
Section: Resultsmentioning
confidence: 99%
“…Proper vaccination technique helps to avoid neurovascular and other anatomic structures such as the subdeltoid bursa, posterior circumflex humeral artery, and the anterior branch of the axillary nerve (5,25,31). The infographic seen in Figure 3 was created by Bancsi et al (32) to help clinicians in proper placement of deltoid vaccines.…”
Section: Key Findings/resultsmentioning
confidence: 99%
“…O tempo médio desde o início da dor até a última consulta de acompanhamento foi de 8 meses (DP AE 13,0; intervalo 1-42). O IMC médio foi de 25,1 (DP AE 4,6; intervalo [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Em relação ao tabagismo, 5 pacientes nunca fumaram, 1 paciente era fumante e 3 pacientes, ex-fumantes.…”
Section: Resultados População Do Estudounclassified
“…Uma revisão sistemática recente demonstrou que apenas três publicações incluíam mais de três pacientes. 29 13 analisaram informações de um banco de dados, dessa vez do Sistema Espanhol de Farmacovigilância. Novamente, o tempo entre a vacinação e o início do tratamento não era conhecido e, neste caso, os tratamentos não foram relatados.…”
Section: Discussionunclassified
See 1 more Smart Citation